Chylothorax in the Setting of Lung Malignancy - Avinash Vangara MD; Moeez Haroon MD; Kathleen Kalafatis DO; Sandhya Kolagatla MD; SubramanyaShyam Ganti MD; Opal Prevatt MD (SAGE Publishing, 2023)
Chylothorax refers to chyle within the pleural space, which frequently arises from an interruption in the thoracic duct or because of reduced lymphatic drainage. Pleural fluid that is white/milky in appearance, with a triglyceride concentration of greater than 110 mg/dL, strongly supports the diagnosis of chylothorax. Chylothorax is nearly always exudative. Transudative chylothorax is extremely rare and typically presents due to a secondary cause, such as liver cirrhosis, nephrotic syndrome, or congestive heart failure. We present a case of chylothorax that occurs in the setting of lung adenocarcinoma. A 65-year-old African American man with a past medical history of metastatic right lung adenocarcinoma presented with dyspnea and palpitations. He denied fever, orthopnea, and paroxysmal nocturnal dyspnea. Therapeutic drainage of the left pleural effusion resulted in 650 mL of milky-white fluid. Pleural fluid analysis demonstrated a triglyceride concentration of 520 mg/dL, a pleural/serum protein ratio of 0.41, a pleural/serum lactate dehydrogenase (LDH) ratio of 0.26, a total pleural LDH of 127 IU/L, and a cholesterol level of 58 mg/dL. This effusion can be classified as transudative as per Light's criteria and exudative as per Heffner's and pleural cholesterol criteria. A subsequent pleural fluid cytology found malignant cells consistent with lung adenocarcinoma. Malignancy is the most common cause of nontraumatic, exudative chylothorax. Light's criteria misinterpret about 25% of transudative effusions as exudative. Therefore, to minimize this error, a combination of the 3-criterial consideration is ideal.